The Effect of Physical Activity Patterns on the Vital Capacity of Nursing Students at the Maluku Ministry of Health Polytechnic - Dunggio, Abdul Rivai Saleh (International Journal of Health Sciences, 2025)
Background: Regular physical activity has been shown to improve organ function, including the lungs. Vital lung capacity (VLC) is an important indicator of respiratory health. Nursing students often have a high academic load, potentially reducing physical activity. Objective: To determine the effect of physical activity patterns on vital lung capacity of nursing students at the Maluku Ministry of Health Polytechnic. Methods: This was a quantitative analytical study using a cross-sectional approach. A sample of 80 students was drawn using purposive sampling. Physical activity was measured using the International Physical Activity Questionnaire (IPAQ), while vital lung capacity was measured using a digital spirometer. Results: There was a significant relationship between physical activity patterns and vital lung capacity (p<0.05). Students with moderate-to-high activity levels had higher average VLC values (3.7±0.5 L) compared to those with light activity levels (2.9±0.4 L). Conclusion: Physical activity patterns significantly influence vital lung capacity. It is recommended that students maintain regular physical activity to support respiratory health.